Conduction and convection phenomena through a slab with thermal heterogeneities - Tadeu, A. (2007)
This paper addresses the computation of the three-dimensional transient heat transfer through a layered solid and/or fluid formation containing irregular inclusions. The use of appropriate Green's functions for a flat layer formation in a boundary element method formulation avoids the discretization of the layer interface boundaries.